A számvevőszékek és a civil szféra kapcsolata az ellenőrzések hatásosságának növelésére - Nagy, Sándor (Jelenkori Társadalmi és Gazdasági Folyamatok, 2011)
The Supreme Audit Institutions (SAI) have to face several challenges: growing expectations from stakeholders, higher pressure on audit efficiency and in the same time (relative) decreasing financial resources and capacities. The cooperation with civil organizations could generate advantages and more added value of the audit activity. A certain civil organization - owing to its features - could deliver relevant, cheap information and offer available additional professional capacity to the SAI. This promising cooperation has constraints and risks too, which must be managed by the national Supreme Audit Institution. An optimized mixture of the cooperation contribute to the effectiveness of the audit activity.